This is an impossible equation. If sqrt(x) = sqrt(x), and sqrt(x) + 2 = sqrt(x) + 12, then that would mean that 2=12, which is incorrect.
Answer:
A1/ ∛m
Step-by-step explanation:
m ^ (-1/3)
this is m to the cubed root in the denominator
1/ ∛m
<u>27 = 6x + 4y </u>= 1 7/20 = 3 4/5<u>
</u>20 = 2x + 5y<u>
</u>
Answer:
![(x + 5) ^{2} + {(y - \frac{1}{2}) }^{2} = 1](https://tex.z-dn.net/?f=%28x%20%2B%205%29%20%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%20%20%5Cfrac%7B1%7D%7B2%7D%29%20%7D%5E%7B2%7D%20%20%3D%201)
Step-by-step explanation:
the formula of a circle is
![{(x - h)}^{2} + {(y - k)}^{2} = {r}^{2}](https://tex.z-dn.net/?f=%20%7B%28x%20-%20h%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%20k%29%7D%5E%7B2%7D%20%20%3D%20%20%7Br%7D%5E%7B2%7D%20)
knowing the values of h, k, and r we can substitute them into the formula
knowing the
98^2 = (100-2)^2
Using (a-b)^2, we have
= (100)^2-2(100)(2)+(2)^2
= 10000-400+4
= 10004-400
= 9604
The answer is 9604.
Please mark me Brainliest